The Judiciary in Africa - Aguda, Dr. T. Akinola (Tufts Archival Research Center, 2005)
Volume 9, Issue 1. Winter Dr. T. Akinola Aguda has since 1978 been Director of the Nigerian Institute for Advanced Legal Studies in Lagos. In addition to his academic experience, Dr. Aguda has held numerous judicial posts, including Chief Judge of the Ando State and the Western State of Nigeria, Chief Judge of the Republic of Botswana, Judge of Appeal of the High Court of the Kingdoms of Lesotho and Swaziland, and his current post of Judge of Appeal of the High Court of Justice of Botswana. In his article, Dr. Aguda examines the potential power which members of the judiciary in Africa can derive through a constitutionally-based system of government for the administration of justice according to the rule of law. He analyzes the inherent and practical limitations upon this power which may be felt in cases of opposition by the executive branch, constitutional crisis, as in revolutionary states, and suppression of judicial autonomy, as may occur in one-party states. Having presented these theoretical points, Dr. Aguda cites numerous examples drawn from anglophone Africa to illustrate both the practical impact of the judiciary in upholding the rule of law and the factors which mitigate against the judge's contribution to the building of social justice on that continent.